Social Education in the Perspective of QS Al-Mā‘ūn and QS Al-Baqarah Verse 271 through Roland Barthes’ Semiotic Approach - Musonif, Irfan; Pranoto, Ahmad Hadi; Ansori, Inamul Hasan; Munis , Ibnu Da’i (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
This study aims to analyse verses from the Qur'an through Roland Barthes' semiotic approach, specifically QS. al-Mā‘ūn dan QS. al-Baqarah [2]: 271. Surah al-Mā‘ūn was chosen because it highlights social issues such as caring for orphans and the poor, while QS. al-Baqarah [2]: 271 emphasising the value of sincerity in almsgiving. This research method is qualitative in nature with a literature review approach, using primary sources in the form of the Qur'an and classical interpretations, as well as secondary sources in the form of recent academic literature. Data analysis was conducted using Barthes' semiotic framework, which encompasses three levels of meaning: denotation, connotation, and mythology. The results of the study indicate that al-Mā‘ūn semiotically presents a critique of formalistic religiosity that is not oriented towards social concern, while QS. al-Baqarah [2]: 271 presenting almsgiving as an ideological symbol of social justice distribution. This study contributes to the development of contemporary interpretation methodology by presenting semiotics as an interdisciplinary approach, as well as affirming the relevance of the Qur'an in building public ethics in the modern era.